Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Ask your questions and receive precise answers from experienced professionals across different disciplines. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
y=-3/16(x-8)^2+12
Step-by-step explanation:
Refer to the vertex form equation for a parabola:
y=a(x-h)^2+k where (h,k) is the vertex.
Therefore, we have y=a(x-8)^2+12 as our equation so far. If we plug in (16,0) we can find a:
0=a(16-8)^2+12
0=64a+12
-12=64a
-12/64=a
-3/16=a
Therefore, your final equation is y=-3/16(x-8)^2+12
Answer:
y = (-5.33)(x - 8)^2 + 12
Step-by-step explanation:
The graph is a parabola which opens down and has its vertex at (8, 12). We can immediately write y = a(x - 8)^2 + 12, knowing that if x = 8, y = 12. To find the coefficient '1', substitute 16 for x and 0 for y:
0 = a(16 - 8)^2 + 12, or
-64a = 12, or a = -64/12 = 5.33
Then the desired function is:
y = (-5.33)(x - 8)^2 + 12
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.